SYNTHESIS AND CHARACTERIZATION OF WATER SOLUBLE CHITOSAN SUCCINATE AS DURABLE ANTIMICROBIAL AGENT ON COTTON - , Noerati, C. L. Radiman,S. Achmad, and I.M.Arcana ([Yogyakarta] : Fak. MIPA Universitas Gadjah Mada, 2007)
Textile products having a prolonged contact with the skin on warm and humid spots are an excellent habitat for all kinds of undesired micro-organisms. When micro-organisms multiply in clothing, they may adversely affect human health such as Staphylococcus aureus, which cause athlete&rsquo